2018
DOI: 10.5271/sjweh.3787
|View full text |Cite
|
Sign up to set email alerts
|

Occupational and leisure-time physical activity differentially predict 6-year incidence of stroke and transient ischemic attack in women

Abstract: The results of this study show that high levels of occupational physical activity increase the risk of stroke and transient ischemic attack in women, while high levels of leisure-time physical activity decrease risk for these diseases. These findings corroborate the physical activity health paradox for the first time with respect to cerebrovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 68 publications
1
41
1
Order By: Relevance
“…A reason for the inconsistent results reported in the literature may be the different assessment and categorization of occupational physical activity, as demonstrated by our comparison of the results from MONICA and NRP1A, and by the analyses using a different categorization in this publication compared with an earlier publication . Furthermore, as shown in our sensitivity analyses stratified by blood pressure and also in previously published studies that stratified analyses by baseline CVD, such potential effect modifiers may substantially change the observed effects of occupational physical activity on (CVD) mortality. Ideally, future studies will consider such factors to aid in developing individualized physical activity recommendations depending on CVD status and related risk factors, such as blood pressure.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…A reason for the inconsistent results reported in the literature may be the different assessment and categorization of occupational physical activity, as demonstrated by our comparison of the results from MONICA and NRP1A, and by the analyses using a different categorization in this publication compared with an earlier publication . Furthermore, as shown in our sensitivity analyses stratified by blood pressure and also in previously published studies that stratified analyses by baseline CVD, such potential effect modifiers may substantially change the observed effects of occupational physical activity on (CVD) mortality. Ideally, future studies will consider such factors to aid in developing individualized physical activity recommendations depending on CVD status and related risk factors, such as blood pressure.…”
Section: Discussionmentioning
confidence: 66%
“…Results of the present study are partly in line with these studies suggesting detrimental effects of occupational physical activity for men. In the most recently published prospective study of 31 270 US working women, prolonged standing at work and higher intensity levels of occupational physical activity were associated with increased risks of 6‐year incidence of both stroke and transitory ischemic attacks while leisure‐time physical activity showed inverse associations, confirming for the first time the physical activity health paradox among women …”
Section: Discussionmentioning
confidence: 83%
“…From a health promotion perspective, it can therefore be concluded that simply increasing the apprentices' volume of PA (even more) is probably not an effective strategy for promoting the health of this target group. The so-called PA paradox assumes that the amount of PA within the occupational context is even likely to exert a detrimental influence on workers' health [35][36][37][38]. A recent article discussed that too low intensities, too long activity durations, insufficient recovery times, inadequate postures, and a low activity control may lead to this negative effect [39].…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation might be that apprentices of these two sectors amass too much activity over the course of their day, which is in line with findings from the first study. This constellation, especially when the percentage of occupational PA is high [35,37], could carry the middle-term risk of physical and mental overload. This could have impaired the work ability and health status of very physically active individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A gender effect seems associated with the OPA level's health effects with less deleterious effect and no increase of mortality in women, 8 even if a very recent study showed a positive relation between the level of OPA and the risk of cerebrovascular disease in women. 12 The high level OPA deleterious effect reported seems to concern specifically CVD and does not appear to affect the incidence of cancer and metabolic diseases. 8 A lower mortality rate is reported in farmers, a job that is associated with a high level of OPA, than in other workers.…”
Section: François Carrémentioning
confidence: 88%